2018
DOI: 10.1590/1983-21252018v31n322rc
|View full text |Cite
|
Sign up to set email alerts
|

Emergence, Growth, and Production of Colored Cotton Subjected to Salt Stress and Organic Fertilization

Abstract: The semi-arid region of Northeast Brazil is vulnerable to problems of water scarcity and salinity, resulting in low-quality irrigation water and the need to adopt cultivation strategies that make the production system viable. Given the above, this study aimed to evaluate emergence, growth, and production of colored cotton subjected to increasing levels of irrigation water salinity and organic matter doses. The experiment was carried out in a eutrophic Regolithic Neosol with a sandy loam texture in a greenhouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…In the interaction between the sources of variation, the increases in organic matter dosages together with irrigation water salinity levels interfered significantly (p<0,01) in fresh shoot mass. In a study by Souza et al (2018) in the cotton crop, only the stem diameter parameter presented significant interaction when evaluating salinity levels and organic matter doses.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In the interaction between the sources of variation, the increases in organic matter dosages together with irrigation water salinity levels interfered significantly (p<0,01) in fresh shoot mass. In a study by Souza et al (2018) in the cotton crop, only the stem diameter parameter presented significant interaction when evaluating salinity levels and organic matter doses.…”
Section: Resultsmentioning
confidence: 91%
“…Regarding the number of leaves and fruits, the evolution was similar to the growth of the plants in height and diameter of the stem, it is observed that the organic matter doses from 4% provided increases in these variables with the emission of leaves and fruits by the cotton plants. For Souza et al (2018) the addition of organic matter promotes increased growth and cotton production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic matter application in substrate composition in the adequate quantity to plants is important and can influence their growth and development. According to Souza et al (2018), it is fundamental to carry out research to provide data on the amount of organic matter required to meet the nutritional needs of the crop under semi-arid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of growth in plants subjected to salt stress was a consequence of changes in leaf gas exchange (gs, E, Ci, and A). In addition, another factor that contributed to the reduction in SD was the decrease in the osmotic potential of the soil solution caused by excess soluble salts in the root zone, which limits the absorption of water by the roots, causing the plant to reduce stomatal opening as a mechanism to reduce water loss, which leads to a reduction in cell turgor and, as a consequence, a decrease in cell expansion and plant growth (Souza, Lima, Gheyi, Nobre, & Soares, 2018). Corroborating the results obtained in this study, F. V. da S. Sá et al (2015) evaluated the initial growth of custard apple (Annona squamosa L.) seedlings as a function of water salinity (ECw from 0.3 to 4.8 dS m -1 ) and observed that an ECw higher than 0.3 dS m -1 caused negative effects on the growth in stem diameter.…”
Section: Stomatal Conductance Of Custard Apple Plants Was Significantly Affected By the Interaction Betweenmentioning
confidence: 99%